COMPOSIÃ‡ÃƒO EM ÃCIDOS GRAXOS DA GORDURA DE ALGUNS PEIXES FLUVIAIS - Fonseca, H.; Gutierrez, L. E.; Nogueira, J. N. (REVISTA DE AGRICULTURA, 2020)
COMPOSIÃ‡ÃƒO EM ÃCIDOS GRAXOS DA GORDURA DE ALGUNS PEIXES FLUVIAIS